Hot topics in infection and immunity in children. editors. - Curtis, Nigel; Finn, Adam 1959-; Pollard, Andrew J. (Advances in experimental medicine and biology, 2011)
Course covers topics in infectious diseases in children and is intended for Pediatric Infectious disease trainees, trainers, and all those who manage children with infections.